Another de novo mutation in the SOD1 gene: the first Turkish patient with SOD1-His47Arg, a case report - Bayraktar, Elif; Çiftçi, Vildan; Uysal, Hilmi; Başak, A. Nazlı (Frontiers in Genetics, 2023)
Amyotrophic lateral sclerosis (ALS) is a fatal, progressive neurodegenerative disease of motor neurons. Most ALS cases are considered sporadic due to the presence of a combination of environmental and complex genetic risk factors, while approximately 10% of cases have a family history. Pathogenic variants in the SOD1 gene are the second most frequent causative of geneticsbased ALS worldwide, after C9ORF72 hexanucleotide repeat expansion. De novo occurrence of pathogenic mutations in ALS-associated genes and its effect on disease progression has been studied before, especially in the FUS gene. Recent studies have shown that a very small portion of SOD1 cases occurred de novo. Here we present the first de novo case of the SOD1 His47Arg mutation in a young female patient with mild symptoms and a slow progression for seven years now.